Maladaptive neuropathological syndrome of blood vessel aging - A. A. Artemenkov (Российский кардиологический журнал)
This article discusses the relationship between maladaptation and blood vessel aging. The work shows that upright posture created an additional load on the circulatory system, and the lifestyle of a modern human is an additional risk factor of cardiovascular diseases. It has been suggested that a disorder of the nervous regulation of vascular tone is the main etiopathogenetic mechanism of morphofunctional changes in blood vessels and their aging. We discussed the statute that vascular reactions in humans is based on the formation of a maladaptive circuit in the cerebral cortex, consisting of a matrix of motor, sensory and associative cortical neurons involved in the maladaptive process. This hypothesis is based on the fact that any irritations entering the cerebral cortex from the periphery (thermal, pain, and others) cause cortical-vascular reflex reactions that change their tonic activity. Based on this principle, a model of vascular aging is further constructed, which is based on the maladaptive damage to all layers of the vascular wall (intima, media and adventitia). The opinion is expressed about the need for early diagnosis and prevention of vascular disorders to maintain human health. In conclusion, it is concluded that if the age of a person is really determined by the age of his blood vessels, then in order to achieve active longevity it is necessary to normalize the relationship in the adaptation-maladaptation-environment. Detailed study of hypertrophy and calcification of blood vessels is needed, since aging always reveals vascular wall thickening and stiffness increase.